Diagnostic endocrinology - Moore, W Tabb (Mosby, 1996)
The book contains the chapters emphasizing new tests and procedures in endocrinology. It discusses subclinical hyperthyroidism and hypothyroidism of development of the third generation assay for TSH; gives understanding and using hemoglobin A1c in the management of type 1 diabetes with the results of the DCCT study; discusses the changes in the testing of inherited medullary thyroid cancer using the RET protooncogens; notes the use of radiolabeled somatostatin analogs to diagnose neuroendocrine and other tumors with a tabulation of currently available results. In addition, the book also deals with the gastrointestinal hormones and their disease manifestations; deals with bone diseases discussing the use of bone markers, the various types of bone densitometry, and bone biopsies